PROFILING TRANSFORMATIONAL LEADERSHIP’S ROLE IN MODELLING THE EFFECT OF SAFETY CLIMATE ON NURSES’ SAFETY PERFORMANCE - Nadwatul Husna Mustapha; Mazlina Malek (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study examines the role of transformational leadership in improving employee safety through elements of motivation, guidance, enforcement, and support for employees, as well as enforcement and monitoring. Transformational leadership serves as a key factor influencing employee safety behaviour and performance. By providing inspiration, guidance, and positive role models, transformational leaders can strengthen safety practices in the workplace and ensure employees constantly adhere to established safety procedures. The study also emphasizes the significance of support to workers through ongoing training, adequate rest, and recognition of their efforts, all of which contribute to improved workplace safety. In addition, effective safety policy enforcement and monitoring through awareness campaigns also play an essential role in ensuring employee compliance. The results of this study reveal that transformational leadership increases employee motivation and strengthens the enforcement of safety policies, ultimately leading to increased employee safety as a whole.